Alert and Ready - Paul, Christopher; Thie, Harry J.; Webb, Katharine Watkins; Young, Stephanie; Clarke, Colin P. (RAND Corporation, 2023)
Over the past decade, especially, U.S. Marine Corps (USMC) intelligence has had to tailor its organization to meet the evolving demands of the operational environment. This has resulted in a number of ad hoc arrangements, practices, and organizations. A broad review of the organizational design of USMC intelligence examined how to align it efficiently and effectively with current and future missions and functions.